Phosphorus adsorption and release dynamics in calcareous soil as affected by humic and fulvic acids - Aswad, Aswad H.; Hamid, Mohammed M.; Almeekh, Mohammad Tarkhan Abo; Ajeel, Mohammed R. (Brawijaya University, 2026)
Humic and fulvic acids play a crucial role in enhancing phosphorus retention in calcareous soils. These organic acids increase phosphorus fixation on soil surfaces, thereby strengthening its binding and modifying its availability in the soil solution. Among the tested treatments, Fulvic Acid at 50 kg ha?¹ (F2) demonstrated the highest adsorption capacity, followed by Humic Acid at 50 kg ha?¹ (H2). Lower doses (H1 at 25 kg ha?¹ and F1 at 25 kg ha?¹) showed adsorption patterns that deviated from the Langmuir model, reflecting heterogeneity in binding sites. Increasing the dose revealed that fulvic acid consistently exhibited greater phosphorus uptake than humic acid. By enhancing both phosphorus storage and supply, fulvic acid improves nutrient use efficiency and supports agricultural productivity. Among the tested isotherm models, Freundlich and Dubinin–Radushkevich provided the best fits, indicating predominantly physical, reversible adsorption mechanisms. These findings suggest that the application of fulvic acid is effective for improving phosphorus retention in soils with similar calcareous properties. Further field trials are recommended to validate these laboratory results under practical agricultural conditions.